A Literary Form for Love: Yves Navarre's My Friends Are Gone with the Wind - Richard M. Berrong (Studies in 20th & 21st Century Literature, 2004)
In My Friends Are Gone with the Wind (Ce sont amis que vent emporte, 1991), one of his last and most innovative texts, Yves Navarre (1940-1994), one of the most important contemporary French novelists to deal significantly and regularly with gay themes, returns to his preoccupation with the dangers that the forms inherent in traditional literary narrative pose for the expression of authentic human experience. The narrator, Roch, wants to capture the reality of his love for David, in part to prove to what he sees as a largely hostile heterosexual world that gays are as capable of loving relationships as straights, in part to show those often inhibited straights how to express their love. He realizes that love's excessive nature requires a literary form that throws off the shackles of traditional order and chronology, so he allows memory to erupt within his manuscript as it occurs, unordered by logic. In the process, Roch accepts that he has to let everything in, even David's infidelities, but that by capturing the truth of love, its impulsive nature, he will convey their love in such a powerful way that it will testify convincingly throughout time to their feelings for each other.
Keywords: My Friends Are Gone with the Wind; Ce sont amis que vent emporte; Yves Navarre; contemporary French novelists; French; gay themes; gay; human experience; Roch; David; love; express; hostile heterosexuality; heterosexual; inhibited; memory; relationship; gay relationship